O011 An analysis of cost effectiveness and clinical outcomes of elective abdominal aortic aneursym repair in a tertiary centre over one year. (22nd July 2022) - Songra, L; Baker, D; Davis, M; Constantinou, J; Hamilton, H; Agu, O; Hynes, N
Abstract: Introduction: Endovascular aneurysm repair (EVAR) is an alternative to open surgical repair (OSR) of abdominal aortic aneurysms (AAA) and has a superior short-term safety profile. However recent guidelines have questioned its long-term cost-effectiveness. We retrospectively compared EVAR, Fenestrated EVAR (FEVAR) and OSR of non-ruptured AAA in a tertiary centre over 12 months, to determine whether FEVAR represents an affordable, clinically efficacious option in aortic repair Methods: Data was collected from the National Vascular Registry and hospital records.73 patients underwent primary elective AAA repair. Patients were followed up for one year post-operatively. The primary outcome was cost per QALY. Secondary outcomes included 30-day mortality and morbidity, aneurysm-related mortality, re-intervention rates, length of hospital stay and all-cause mortality at one year. Results: Cost per QALY was calculated as £19134.75, £15408.00 and £12118.16 for FEVAR, EVAR and OSR respectively (FEVAR vs EVAR p= 0.438, FEVAR vs OSR p= 0.001, OSR vs EVAR p= 0.589) OSR was associated with a longer overall hospital and ITU stay, and significantly higher incidence of respiratory complications post-operatively compared to FEVAR and EVAR. FEVAR was associated with significantly higher operative costs, and higher re-intervention and readmission rates compared to EVAR and OSR. There was no significant difference between perioperative and one year mortality between the repair options. Conclusion: FEVAR is more expensive than OSR but based on NICE willingness-to-pay thresholds, it still presents a viable alternative for aortic repair, when performed in specialist centres. However, long term data is required to make informed decisions on cost-effectiveness. Take-home message: FEVAR represents a viable alternative for elective abdominal aortic repair. Long-term RCT data are required to make informed decisions on cost effectiveness